Green public procurement and sustainable development: the case of social welfare centres from the Łódź Province in Poland - Szydłowski, Cezary (Władza Sądzenia, 2023)
The aim of the article is to discuss the issue of green public procurement in the context of public contract award procedures applied by social welfare centres from the Łódź Province (voivodeship) in Poland. The topic is set against the backdrop of the existing theories of green public procurement, a circular economy and sustainable development. The author applies the case study method, analytical methods, inference-based methods, source document study and literature review. The author explores the hypothesis that social welfare centres in the Łódź Province are reluctant to apply the green public procurement (GPP) approach or use environmental (GPP) criteria to evaluate tenders submitted by economic operators under the public procurement procedure. The study focuses on notices published by social welfare centres from the Łódź Province in the Public Procurement Bulletin from 1 January 2023 to 30 September 2023. The examination of 20 contract award procedures revealed that environmental aspects were mentioned in 2 tenders. It is noteworthy that both tenders referred to passenger transport services procured by the same social welfare centre. The results of the analysis corroborate the hypothesis that GPP was used to a limited extent. Therefore, public authorities should undertake measures to promote green public procurement as compatible with the concept of sustainable development.